Кам’яні комплекси верхньопалеолітичної стоянки Бужанка 2. Варіанти використання сировини - Ступак, Д.В. (Археологический альманах, 2009)
In 2003 year in Middle Desna region was discovered new Epigravettian site Buzhanka 2. Typologically tool complex of Upper layer is closely to Mezhirich type of industry. Thus, Buzhanka 2 is more northern site within this type of industry. The Upper layer 1 and Lower layer belong to Epigravettian techno-complex. Unfortunately, the little number of tools doesn’t give possibility for more exact cultural definition. The Upper layer is dated for 14350 ± 60 BP, GrA-38555. The stone assemblages from all layers are subdivided on three raw material groups: flint, quartzite and argillite. The very big percentages of quartzite in Upper layer 1 (42,8%) and Upper layer (45,7%) probably is resulted by the on-site transportation of small blocks. The volume of flints blocks was enough to produce the main types of tool, but the size of flint nodules does not give the possibility for big size and number of blades. That is why, the big size of blades were done from quartzite. In Lower layer the predomination of flint can be explain by specific character of investigated part of site. Probably, blocks of argillite transported on the site with blocks of other kind raw materials and, after testing, were not used.